Thinking about the world : building geography foundations - Brown, Lawrence W. (Menlo Park, California : Addison-Wesley, 1993)
Why does it seem our earth doesn't have enough resources? Why so much violence on the planet? How does the Earth's geography influences the distribution of money, food, religion, population, and power?
Keywords: Geography